Nexus of crude oil and clean energy stock indices: Evidence from time-vector-auto-regression in conjunction with conditional-autoregressive-value-at-risk - Nader Trabelsi; Aviral Kumar Tiwari; Fahmi Ghallabi; Imen Khemakhem (Heliyon)
The current study aims to elicit information regarding the tail risk transmission mechanism between crude oil (CO) and selected clean energy (CE) stock indices across time and during certain economic events. A Time-Varying Parameter Vector Auto-Regressive model (TVP-VAR) paired with the conditional autoregressive value-at-risk (CAViaR) approach was used to investigate data from January 1, 2015 to December 29, 2022. Overall, we show that an increased vulnerability to tail risk and deficits might be linked to dynamic spillover over examined markets. We also provide evidence that connectedness rises during significant crisis situations, and the last epidemic has the potential to make a lasting impact on the various marketplaces of concern. According to the return and conditional variance time-series, CE stock indices are the most important source of return shocks to CO. However, the CO is the primary cause of volatility in CE stock indices. During the recent virus pandemic, the most significant volatility shock transmissions from CO to CE stock indices occurred. During the Russia-Ukraine war, volatility shocks to CO were mostly caused by CE stock indices. The results of our study offer concrete consequences and new perspectives to various market players in order to improve the management and understanding of risks.